(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article analyzes the exchange of cultural heritage of the peoples of Uzbekistan and Kyrgyzstan in the traditional cultural and spiritual sphere after independence. Since then, special attention has been paid to the restoration of history, culture and traditions. International cultural events have contributed to the exchange and mutual enrichment of the cultures of fraternal peoples. In the context of independence, forms of cultural cooperation are actively developing: exchange of artists, literary evenings, photo exhibitions and events dedicated to historical dates. These events are held both in Uzbekistan and Kyrgyzstan, strengthening ties between peoples and creating a solid founda-tion for interstate relations. Exchange of creative groups, festivals, competitions and exhibitions expand the range of cooperation, helping to identify interesting productions and strengthen friendship between peoples. Festivals become a platform for popularizing national musical art, preserving and developing traditions, as well as for nurturing love for beauty in young people. It is important to note that such events contribute to deepening mutual understanding and cultural exchange, strengthening cooperation between the two countries.